Projecto de melhoria da logística hospitalar do Hospital Infante D. Pedro - Neves, Rui Pedro Lourenço (2011)
No actual contexto sócio-económico das instituições públicas de saúde, no qual se verifica luta pela sua própria auto-sustentabilidade, é notória a adopção destas, por alguns princípios utilizados pelas melhores organizações industriais, com vista o incremento da competitividade e mesmo da sua sobrevivência no panorama actual. O presente relatório descreve um projecto de melhoria da gestão logística hospitalar do Hospital Infante D. Pedro em Aveiro, Portugal. ABSTRACT: In the actual socio-economical context of the health public institutions, in which a struggle to keep its own sustainability is being maintained, it is noticeable the use and adoption of some principles used by the best industrial organizations nowadays. The aim is to increase their competitiveness or even their survival, especially now, in the present difficult environment. The present report describes a project of improvement in the logistics management, in the Hospital Infante D. Pedro located in the city of Aveiro, Portugal.